Metaverse in marketing: role of performance expectancy and social influence on consumer expectation to ethical conduct - Rafia Rafa, Fadia (2024)
This thesis investigates the impact of performance expectancy and social influence on consumer expectations to ethical conduct by metaverse operators. Grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT), the study explores how these factors shape consumer expectations in emerging digital environments. The research employs a quantitative methodology, utilizing surveys to collect data from over 100 Metaverse users. The findings reveal that performance expectancy significantly influences consumer expectations, emphasizing the importance of efficiency and effectiveness in virtual environments. However, social influence is found to be insignificant, suggesting that consumers prioritize their ethical considerations over peer or societal norms. From a practical perspective, the study offers valuable insights for Metaverse platform developers, marketers, and regulators. It highlights the need for developing highly efficient and effective technological solutions and emphasizes the importance of direct communication. Personalized marketing that demonstrates tangible benefits and ethical practices is likely to be more effective in the Metaverse. The research contributes to the ongoing discourse on ethical standards in digital marketing and suggests areas for future research, such as the impact of cultural differences on ethical attitudes and consumer trust, the evolution of consumer behavior over time, and the effects of enhanced security and privacy features on user trust. By addressing these aspects, the thesis aims to guide the development of more ethical and effective Metaverse marketing strategies, fostering greater consumer engagement and satisfaction.